FEATURES OF DESIGNING PRECAST-MONOLITHIC BRIDGE SPANS - Koval, P. M.; Fal, A. E.; Marchuk, S. M. (Science and Transport Progress, 2010)
The calculation results for assembling monolithic spans are described. The data obtained during calculations are analyzed; the necessity of calculation of spans of this type at a few stages of including separate elements into work is determined. The comparative calculation of spatial models in the LIRA SOFTWARE is conducted.